Pinpointing the Geographic Origin of 165-Year-Old Human Skeletal Remains Found in Punjab, India: Evidence From Mitochondrial DNA and Stable Isotope Analysis - Sehrawat, J.S.; Agrawal, Shailesh; Sankhyan, Deeksha; Singh, Monika; Kumar, Sachin; Prakash, Satya; Rajpal, Richa; Chaubey, Gyaneshwer; Thangaraj, Kumarasamy; Rai, Niraj (Frontiers in Genetics, 2022)
In 2014, 157 years after the Sepoy Mutiny of 1857, several unidentified human skeletons were discovered in an abandoned well at Ajnala, Punjab. The most prevailing hypothesis suggested them as Indian soldiers who mutinied during the Indian uprising of 1857. However, there is an intense debate on their geographic affinity. Therefore, to pinpoint their area of origin, we have successfully isolated DNA from cementum rich material of 50 good quality random teeth samples and analysed mtDNA haplogroups. In addition to that, we analysed 85 individuals for Oxygen isotope (δ18O values). The mtDNA haplogroup distribution and clustering pattern rejected the local ancestry and indicated their genetic link with the populations living East of Punjab. In addition, the Oxygen isotope analysis (δ18O values) from archaeological skeletal remains corroborated the molecular data and suggested the closest possible geographical affinity of these skeletal remains towards the Eastern part of India, largely covering the Gangetic plain region. The data generated from this study is expected to expand our understanding of the ancestry and population affinity of martyr soldiers.